Bilayer dielectric composites with positive-ε and negative-ε layers achieving high dielectric constant and low dielectric loss. (September 2022) - Song, Xiaoting; Fan, Guohua; Liu, Dong; Wei, Zaixin; Liu, Yao; Fan, Runhua
Highlights: A novel design of bilayer composite is prepared with positive-ε and negative-ε layers. The introduction of negative-ε layer realizing the permittivity boost. The positive-ε layer provides low dielectric loss via adding BN sheets. The design strategy has great importance in exploration of energy storage materials. Abstract: Polymeric dielectric materials with high permittivity, low dielectric loss and excellent breakdown strength enable the development of advanced energy storage capacitors. However, enhanced permittivity is always accompanied by increasing dielectric loss, which significantly limits the practical applications and deserves considerable concern. Targeting at realizing simultaneous high permittivity, moderate breakdown strength and low loss, the unique design of bilayer composites composed of positive- ε layer and negative- ε layer are investigated in this work. The positive-ε layer provides low dielectric loss and offers moderate breakdown strength, while the negative-ε layer supplies high permittivity. Especially, the permittivity of 15 %BN/PVDF-40 %MWCNTs/PVDF composite is increased to 292 along with the low loss of 0.028@10 kHz. Insights into how the breakdown strength and max energy density of bilayer composites were discussed here. And the modulation of bilayers structure with positive- ε layer and negative- ε layer provides a new way to realize the dielectric properties and energy storage performance.